Simplified link reliability schemes for voice over ip over wireless networks - Lim, Boon Hoi (Universiti Malaysia Sarawak, (UNIMAS), 2013)
With the high demands for mobility and flexibility, the market for wireless network is taking off rapidly. This had urged the extensive growth of Voice over Internet Protocol (VoIP) application for today’s Internet as well. Due to the fundamental problems that arises in the transmission and reception voice packet over the wireless link conforming to IEEE 802.11 standards, the packet loss and error can have a major impact perceived voice quality. Therefore, the objective for this research is to propose a Simplified Link Reliability scheme which helps to improve the Quality of Service (QoS) in voice traffic transmission over the wireless networks by minimizing the impact of packet loss and error. This scheme consists of two algorithms, which are the Low Level Frame Prioritisation algorithm and Enhanced Link Reliability algorithm. The Low Level Frame Prioritisation algorithm is to give priority to the voice traffic to transmit at the higher survival rate channels. Whereas, the Enhanced Link Reliability algorithm is to send multiple traffic replications over the high point-to-point bandwidth wireless channel. These two algorithms have been proven able to perform well in enhancing voice quality under specified circumstances via network simulations by reducing the possibility of error occurrence. Hence, the Simplified Link Reliability Enhancement Scheme is a simple algorithm, which is able to improve the real-time traffic in wireless network by reducing error rates. As the real world environments are insufficient for transmission of time sensitive traffic and with the vary performance of VoIP mileage, adoption of this scheme could help improve the QoS of real-time traffic.